Enterprise Resource Planning System Implementation: A Case Study of a Japanese MNC - Chia, Sok Yeen (2007)
Enterprise Resource Planning (ERP) is considered as one of the key technology development in the 1990s. With globalization, organizations find themselves no longer competing solely on price and quality, but on other factors such as on-time delivery and more efficient distribution processes. ERP is the answer to achieving an integrated supply chain and enabling the organization that has successfully implemented ERP to compete in the international arena. However, implementing ERP is often a long and arduous process that requires huge investments in both human and financial resources. Some organizations managed to reap the benefits of the system, while others suffer great losses resulting from the implementation failure. This paper examines the critical success factors of ERP implementation and using the Project Phase Model by Parr and Shanks (2000), it will study how these factors are applicable to a Japanese organization that has successfully implemented SAP. It also tries to further explore factors that may not have been mentioned in the various literatures but have nonetheless affected the implementation process.